Reality and risk: A refutation of S. Rendón's analysis of the Peruvian Truth and Reconciliation Commission's conflict mortality study. (March 2019) - Manrique-Vallier, Daniel; Ball, Patrick
We refute S. Rendón's recent criticism of the 2003 Peruvian Truth and Reconciliation Commission (TRC) conflict mortality study. We first show that his most important result, an alternative estimate of the mortality due to the Maoist guerrillas of Shining Path ( Sendero Luminoso ), is lower than existing observed data and is therefore impossible. We then analyze his statistical approach and find that it is affected by a subtle form of selection bias. We contrast his approach to the TRC's using tools from statistical decision theory, and determine that his method is inadequate for this problem—and that the TRC's approach is, at minimum, better. Without advocating for the TRC's original results, we conclude that Rendón's approach and methods are inferior to the TRC's original work.